Coconut (Cocos nucifera L. Var. Viridis.) farming efficiency in Central Sulawesi: technical, allocative, and economic - Rustam Abd Rauf; Lien Damayanti; Erny; Shintami R. Malik; Hardiyanti Sultan; Mukhlis (Jurnal Penelitian Pendidikan IPA, 2024)
Coconut farmers in some regions frequently neglect proper agricultural practices, making coconut farming inefficient. The purpose of the study was to analyze economic efficiency, technical efficiency and allocative efficiency of coconut farming. The research method uses descriptive quantitativeThe research location was purposively selected in Parigi Moutong Regency. Technical efficiency was examined using production function analysis, particularly using the stochastic frontier. Meanwhile, allocative and economic efficiency was determined by deriving the dual cost function from production costs. coconut farming was not technically efficient, generating an average value of 79.83%. Two technical factors, education and experience, could potentially reduce technical inefficiency. However, the economic efficiency was nearly efficient, reaching 97.9%, while the allocative efficiency was inefficient, acquiring 78.2%. The calculation of efficiency has been extensively applied in agricultural commodities, including food crops as well as in plantation crops like cocoa. However, currently, these three types of efficiency have not been implemented in the coconut commodity, particularly in Central Sulawesi.